2020
DOI: 10.21037/gs-20-532
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and related risk factors after breast reconstruction in breast cancer patients

Abstract: Background: Breast cancer is the most frequently occurring cancer in women globally, using radical mastectomy as the main clinical treatment. This study aims to investigate the quality of life and related factors in patients after breast reconstruction.Methods: Female patients undergoing breast reconstruction after radical mastectomy between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The results show that the variable age has a significant effect on the symptomatology of survivors in both the EORTC QLQ-C30 and the EORTC QLQ-BR23, where younger women have the highest scores on the scales, except for the items diarrhoea, BRBS andBRHL, with SF, BRSEF, BRSEE, BRFU, BRBS and BRHL being significant items and agreeing with other studies where it was observed that younger women receive more treatment, thus increasing the side effects [ 23 , 48 ]. On the other hand, the symptomatology is higher in the elderly women in BRBRS, BRAS and BRHL, agreeing with two studies where they believe that the main culture/religión and a worse libido generates more symptomatoloy in these items [ 34 , 49 ]. Young women show a significant correlation with the BRFU item ( p = 0.035), where they see worse future prospects than older women, because they are usually the breadwinners or the ones responsible for the children, reporting greater concern for their future health [ 45 , 48 , 50 ].…”
Section: Discussionsupporting
confidence: 77%
“…The results show that the variable age has a significant effect on the symptomatology of survivors in both the EORTC QLQ-C30 and the EORTC QLQ-BR23, where younger women have the highest scores on the scales, except for the items diarrhoea, BRBS andBRHL, with SF, BRSEF, BRSEE, BRFU, BRBS and BRHL being significant items and agreeing with other studies where it was observed that younger women receive more treatment, thus increasing the side effects [ 23 , 48 ]. On the other hand, the symptomatology is higher in the elderly women in BRBRS, BRAS and BRHL, agreeing with two studies where they believe that the main culture/religión and a worse libido generates more symptomatoloy in these items [ 34 , 49 ]. Young women show a significant correlation with the BRFU item ( p = 0.035), where they see worse future prospects than older women, because they are usually the breadwinners or the ones responsible for the children, reporting greater concern for their future health [ 45 , 48 , 50 ].…”
Section: Discussionsupporting
confidence: 77%
“…Studies reported that significant benefits in the quality of life and psychosocial well-being were gained via IBR after mastectomy. Breast reconstruction is increasingly provided as the essential part of postmastectomy rehabilitation ( 13 15 ). The oncologic safety of mastectomy followed by IBR is sufficiently confirmed in patients with early-stage breast cancer ( 7 , 16 – 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally acknowledged that most IPBR-related complications are associated with age, personal medical history (smoking and overweight/obesity) and adjuvant therapy as risk factors. Once these factors had been matched for the subjects of the current study, no significant differences were seen between the two types of surgery [ 13 , 14 ]. Evaluation of postoperative complications revealed that OIPBR patients had a significantly lower incidence of lymphedema on the surgical side ( p = 0.041) and of readmission ( p = 0.040) compared with THIPBR patients.…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed no significant differences between OIPBR and THIPBR groups in any score either prior to surgery or at 3-month follow-up. Factors that influence satisfaction and quality of life after breast reconstruction include age, tumor stage, postoperative complications [ 14 ] and nicotine addiction [ 27 ], but some studies have also shown that postoperative implant complications are not associated with lower quality of life scores [ 28 ]. Nicotine addiction was strongly associated with breast satisfaction.…”
Section: Discussionmentioning
confidence: 99%